Preventive orthodontics treatment with space maintainer in the early loss of deciduous tooth: Perawatan ortodontik pencegahan dengan menggunakan space maintainer pada kehilangan dini gigi sulung - Eka Erwansyah; Rika Damayanti; Sherly Horax; Siti Baiq Gadisha (Makassar Dental Journal PDGI Makassar, 2021)
Background: The development of a child's jaw with complete teeth will certainly be better than the development of the jaw with some teeth that have been lost prematurely because the teeth are lost prematurely is very potentially crowding. This event often occurs during periods of mixed teeth caused by the premature loss of decidui teeth while the replacement teeth have not erupted due to shifting of teeth and so the space for the replacement teeth is insufficient. Objective: To find out more about preventive orthodontic treatments by using a space maintainer on premature loss of decidui tooth. Method: Scientific evidence and clinical cases were taken from the literature to support this review and information on preventive orthodontic treatments using space maintainers on early tooth loss. Conclusion: Orthodontic treatment with space maintainer is an appropriate procedure in case of premature loss to prevent the occurrence of malocclusion caused by tendency to movement of teeth resulting in loss of space for permanent teeth, crowding and impaction.